Medical diseases and depression in older adults: common features and etiological relation - Bastidas-Bilbao, Hamer (2014)
A systematic review was conducted of 51 English-language papers published since 2000 in the following databases: PsycNet, Ebsco, and Science Direct. Findings reveal a high comorbidity of depression in older adults. Moreover, they also exhibit stroke, diabetes, Alzheimer’s disease and Parkinsonism, with patterns of symptoms similar to those seen in depression resulting from disease impairment. Analysis shows that these diseases can also precede depression, even without an anatomical-functional link, due to the psychosocial burden borne by the patient. Depression is also seen as a risk factor for stroke and diabetes. Longitudinal studies are suggested to judiciously characterize etiological paths for depressionmore extensively.